Citywide Inclusive Sanitation—Business as Unusual: Shifting the Paradigm by Shifting Minds - Gambrill, Martin; Gilsdorf, Rebecca J.; Kotwal, Nandita (Frontiers in Environmental Science, 2020)
As the world urbanizes, the challenges of urban sanitation increase, with urban population growth dramatically outpacing gains in sanitation access. Total global costs of inadequate sanitation are estimated at USD 260 billion annually, and reaching the SDG urban sanitation targets will require over USD 45 billion each year. ‘Business as usual’ in urban sanitation – where conventional sewerage and wastewater treatment are considered as the only solution – will not get us to universal safely managed sanitation. Citywide Inclusive Sanitation (CWIS) looks to shift the urban sanitation paradigm, aiming to ensure everyone has access to safely managed sanitation by promoting a range of solutions – both on-site and sewered, centralized or decentralized – tailored to the realities of the world’s burgeoning cities. CWIS means focusing on service provision and its enabling environment, rather than on building infrastructure. This shift in paradigm to CWIS requires a shift in mindsets. Governments and development agencies increasingly recognize that historic approaches to urban sanitation have not always worked and new approaches, such as CWIS, are required. Consulting firms need to think differently, and not simply replicate approaches found in developed countries. Engineering curricula should include the design and management of non-conventional systems and should explore opportunities for leapfrogging to solutions that take full account of the public health and environmental imperatives of urban sanitation. We should rethink the way sanitation infrastructure is funded and challenge approaches that subsidize sewers but not onsite sanitation, that don’t embrace innovation and don’t consider running costs. CWIS, or business as unusual, requires awareness raising and capacity building, the spreading around the world of successful experiences, and the development and use of tools and other resource materials designed to help provide sustainable urban sanitation services to all. At the World Bank we see that shifting mindsets towards CWIS principles can be achieved and that there is a growing appetite globally for embracing such principles. We see an important emerging global movement to engage on CWIS by governments and development partners, which provides an unprecedented opportunity to shift the urban sanitation paradigm in the pursuit of universal safely managed sanitation.